A Legal Analysis of the Handling of Theft Criminal Investigations and the Implementation of Restorative Justice in an Effort to Formulate an Ideal Justice System in Batam City - Muhammad Brata Ul-Husna; Andri Winjaya Laksana (Jurnal Hukum Khaira Ummah, 2025)
Abstract. In the preamble to the 1945 Constitution, paragraph 4, it is emphasized that the national goal of the State of Indonesia is to protect all Indonesian people and all of Indonesia's homeland and to advance general welfare, to educate the nation's life and to participate in implementing world order based on independence, eternal peace and social justice. The implementation of the national goal in order to realize the noble ideals of the Indonesian nation towards a just and prosperous society based on Pancasila and the 1945 Constitution, is realized through the existence of a national development program. Indonesia is a state of law. The affirmation of Article 1 paragraph (1) of the 1945 Constitution is that the state guarantees every Indonesian citizen equal standing before the law. This is regulated in Article 27 Paragraph (1) of the 1945 Constitution which reads: "All citizens have equal standing before the law and government and are obliged to uphold the law and government without exception." In state activities, the law determines everything. The law is the commander. The law is a system of rules. What leads us is that system of rules, not individuals who happen to hold positions. Public office holders come and go dynamically, but the regulatory system is stable and relatively permanent. The statement that Indonesia is a State of Law also has the consequence that Indonesia applies law as an ideology to create order, security, justice, and welfare for its citizens, so that the law is binding on every action taken by its citizens. In every state of law, perpetrators of violations of legal norms are required to be accountable for their actions. Because legal norms are created to be obeyed, if violated, sanctions will be imposed. For example, the State of Indonesia firmly states that Indonesia is a State Based on Law and not based on mere power. From the above definition, it can be concluded that Indonesia is a state of law, where all behavior of its citizens must be guided by existing legal norms. Law functions to regulate relations between one person and another and between humans and the state, so that everything runs in an orderly manner. Therefore, the purpose of law is to achieve peace by realizing legal certainty and justice in society. Legal certainty requires the formulation of clear and firm rules in legislation.